Introduction to Behavioral Science and Its Practical Applications in Public Health; [Introducción a la Ciencia del Comportamiento y Sus Aplicaciones Prácticas en la Salud Pública] - Duarte-Anselmi, G (Medwave Estudios Ltda, 2025)
The World Health Organization (WHO) highlights the importance of improving the design of public health interventions and policies by applying principles from the behavioral sciences. These sciences play a crucial role in modifying behaviors and addressing a wide range of health challenges, from pandemics and chronic diseases to the climate crisis. This article examines the transformative impact of behavioral sciences on public health promotion, focusing on the factors that influence decision-making and intervention strategies based on the six principles developed by the WHO Technical Advisory Group. Additionally, it addresses the significant shortage of Spanish-language literature on this topic, reviewing contributions from influential scientists and key theoretical models. The WHO’s recommendations for the effective implementation of these interventions in public health are also discussed. This work not only fills a critical gap in the Spanish-language literature but also provides practical tools to improve public health in Spanish-speaking countries. © 2025, Medwave Estudios Ltda. All rights reserved.